Potential of Sugarcane in Modern Energy Development in Southern Africa - Souza, Simone P.; Horta Nogueira, Luiz A.; Watson, Helen K.; Lynd, Lee Rybeck; Elmissiry, Mosad; Cortez, Luís A. B. (Frontiers in Energy Research, 2016)
For more than half of the Southern African population, human development is limited by a lack of access to electricity and modern energy for cooking. Modern bioenergy merits consideration as one means to address this situation in areas where sufficient arable land is available. While numerous studies have concluded that Africa has significant biomass potential, they do not indicate by how much it can effectively reduce the use of traditional biomass and provide more accessible energy, especially at a country level. Here, we evaluate the potential of sugarcane to replace traditional biomass and fossil fuel and enlarge the access to electricity in Southern Africa. By using its current molasses for ethanol production, Swaziland could increase electricity generation by 40% using bagasse and replace 60% of cooking fuel or 30% of liquid fossil fuel. Sugarcane expansion over 1% of the pasture land in Angola, Mozambique, and Zambia could replace greater than 70% of cooking fuel. Bioelectricity generation from modest sugarcane expansion could be increased by 10% in Malawi, Mozambique, and Zambia and by 20% in Angola. Our results support the potential of sugarcane as a modern energy alternative for Southern Africa.